Dynamics of antioxident ptotection indices in answer to skeletal, cranial-cerebral trauma and combined traumas in the period of early signs of traumatic disease - Mykhaylyuk, I. A.; Gudyma, A. A. (Journal of Education, Health and Sport, 2015)
Mykhaylyuk I. A., Gudyma A. A. Dynamics of antioxident ptotection indices in answer to skeletal, cranial-cerebral trauma and combined traumas in the period of early signs of traumatic disease. Journal of Education, Health and Sport. 2015;5(4):29-40. ISSN 2391-8306. DOI: 10.5281/zenodo.16591 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A29-40 https://pbn.nauka.gov.pl/works/553130 http://dx.doi.org/10.5281/zenodo.16591 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 15.03.2015. UDC 612.015.11-02:616.711/.714-001-036.4]-092.9 DYNAMICS OF ANTIOXIDENT PTOTECTION INDICES IN ANSWER TO SKELETAL, CRANIAL-CEREBRAL TRAUMA AND COMBINED TRAUMAS IN THE PERIOD OF EARLY SIGNS OF TRAUMATIC DISEASE I. A. Mykhaylyuk, A. A. Gudyma State High Educational Establishment “I.Ya.HorbachevskyyTernopilStateMedicalUniversity” Abstract In answer to skeletal, cranial-cerebral and combined traumas the significant abnormalities of liver tissue antioxidant protection is observed. There comes a significant reduction in the activity of superoxide dismutase, catalase, content of SH-groups compared to the control group. Against the background of cranial-cerebral trauma and combined trauma, the activity of superoxide dismutase and catalase gradually decreases from the 1st to the 7th days, and against the background of skeletal trauma itself it reaches the maximum decrease after 3 days and increase after 7 days without reaching the control level. Maximum abnormalities occur against the background of combined trauma after 7 days of post-traumatic period. The maximum infringement of SH-groups content in all the experimental groups occur up to the 3rd day and are larger in the group with combined trauma. Henceforth the index against the background of all the traumas increases up to the 7th day without reaching control dimensions. In the conditions of modeled traumas the abnormalities of ceruloplasmin content is observed. In all the experimental groups it grows from the 1st to the 7th day and is statistically reliable bigger than in the control group. Key words: skeletal traumas, cranial-cerebral trauma, cranial-skeletal trauma, antioxidant protection, early period of the traumatic disease.